S100A16 cooperates with DEPDC1 to promote the progression and angiogenesis of nephroblastoma through PI3K/Akt/mTOR pathway - Geng, Geng; Xu, Yongtao; Li, Qingfang; Li, Qinghao; Yuan, Lili; Dong, Mengyao; Ming, Ming (Polish Journal of Pathology, 2023)
S100 calcium-binding protein A16 (S100A16) has previously been reported to play a role in tumor cells. Nevertheless, the role that S100A16 played in nephroblastoma cells remains obscure. The expression of S100A16 and DEPDC1 were detected via RT-q PCR and western blotting. Cell transfection was performed to overexpress DEPDC1 or interfere S100A16. CCK8 was applied for the assessment of cell viability. The apoptotic level and the capabilities of WiT49 cells to proliferate, invade and migrated were appraised utilizing Tunel, colony formation Transwell, and wound healing, separately. The angiogenesis was estimated through tube formation assay. Co-immunoprecipitation (CO-IP) was performed to examine the targeted binding of S100A16 to DEPDC1. The contents of PI3K/Akt/mTOR pathway-related proteins were resolved by virtue of western blot. S100A16 and DEPDC1 expression levels were significantly increased in nephroblastoma cell lines. S100A16 deletion suppressed nephroblastoma cell proliferative, invasive, migrative and angiogenetic capabilities but facilitated the apoptotic level. Moreover, S100A16 could bind DEPDC1, DEPDC1 overexpression partially reversed the inhibitory effect of S100A16 interference on nephroblastoma cell. DEPDC1 overexpression also partially counteracted the suppressive impacts of S100A16 interference on PI3K/Akt/mTOR pathway-related proteins. S100A16 synergistic with DEPDC1 promotes the progression and angiogenesis of nephroblastoma cell through the PI3K/Akt/mTOR pathway.